Molecular motor function in axonal transport in vivo probed by genetic and computational analysis in Drosophila. - Reis, G.F.; Yang, G.; Szpankowski, L.; Weaver, C.; Shah, S.B.; Robinson, J.T.; Hays, T.S.; Danuser, G.; Goldstein, L.S. (Molecular Biology of the Cell, 2012)
Bidirectional axonal transport driven by kinesin and dynein along microtubules is critical to neuronal viability and function. To evaluate axonal transport mechanisms, we developed a high-resolution imaging system to track the movement of amyloid precursor protein (APP) vesicles in Drosophila segmental nerve axons. Computational analyses of a large number of moving vesicles in defined genetic backgrounds with partial reduction or overexpression of motor proteins enabled us to test with high precision existing and new models of motor activity and coordination in vivo. We discovered several previously unknown features of vesicle movement, including a surprising dependence of anterograde APP vesicle movement velocity on the amount of kinesin-1. This finding is largely incompatible with the biophysical properties of kinesin-1 derived from in vitro analyses. Our data also suggest kinesin-1 and cytoplasmic dynein motors assemble in stable mixtures on APP vesicles and their direction and velocity are controlled at least in part by dynein intermediate chain.